Optimizing security and flexibility by designing a high security system for e-government servers - Abdul Talib, Yurita Yakimin; Zaidan, B.B; Zaidan, A.A; Naji, A.W. (2009)
E-government is one of the most popular applications in the Web base applications.It helps people to do those work online, access the government sites, apply for online jobs, access to important data from the government database, and on top of that it also helps the government employees to access cameras and sensors over the country. However there are many challenges to keep the government data safe and secure in an open environment (network).Therefore, this paper is proposed to discuss two issues.In the first stage how to keep the data in safe, where this paper introduces many applications that guarantee a very high security for accessing and editing of data.The paper also carries a new design for E-government servers in which the authors try to distribute the security service on each line to avoid any attack from out or inside. The second issue is to ensure the flexibility of the data flow from the servers to the user which is the second challenge in the design.The experiment shows a good expected result, with the new approach have a high security and at the same time flexible E-government access.This paper provides a different view and uses a mixture of technologies to achieve a high security rate that will not affect different user's access.E-Government environment is subject to multiple security challenges, thus this paper proposed a model on how to secure the servers and how to ensure the flexibility of the system, in a simple way balance between a lot of security tools and the appreciate protecting vs. granting the flexible data flow up and download to the user.